2019
DOI: 10.18553/jmcp.2019.25.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Controlled Substance Use Management on Prescribing Patterns and Health Outcomes Among High-Risk Users

Abstract: BACKGROUND: The misuse of prescription drugs is a serious public health problem. Although controlled substance (CS) prescribing, in particular, opioid analgesics, has recently declined, the volume of prescriptions in 2015 was still 3 times higher than in 1999. To curb the high volume of CS prescribing, a national health plan has implemented a controlled substance utilization management (CSUM) program, a prescriber-focused educational intervention regarding patients at risk for CS misuse. OBJECTIVE: To characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…For example, a recent study showed that utilization management leveraging integrated claims for people with a substance use disorder can lower opioid prescription volume and emergency department (ED) visits. 8 study was member enrollment in health plan care management or disease management.…”
Section: ■■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study showed that utilization management leveraging integrated claims for people with a substance use disorder can lower opioid prescription volume and emergency department (ED) visits. 8 study was member enrollment in health plan care management or disease management.…”
Section: ■■ Methodsmentioning
confidence: 99%
“…Lower medical costs may be due to the availability and use of integrated data and benefits for improved care management, chronic condition management, specialty and controlled medication management, improved artificial intelligence and machine learning algorithms to match members to targeted intervention, and improved collaboration in provider partnerships to deliver care. 3,7,8 For example, with integrated data, Cambia care managers target members who could benefit from clinical programs and high-touch services to improve 19.3% versus 21.1%, P < 0.001. As shown in Table 3, after adjustment, odds were 15% lower for hospitalization, P < 0.001, and 7% lower for ED visits, P < 0.001, among the carve-in members.…”
Section: Member Characteristicsmentioning
confidence: 99%